Transreligious Perspectives on Purity in The Earlier Deeds of The Apostles - Marianna Cerno (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2022)
Initially conceived as a research on the concept of purity and the related commonplaces in Latin hagiography prior to the year 1000, the present paper investigates three of the so-called apocryphal Acts of the Apostles, the only hagiographies containing useful data on the proposed topic. In the broader context of late antique and early medieval Latin hagiographical production, the Deeds of Peter and Paul (BHL 6657), James the Less (BHL 4093) and Matthew (BHL 5690) show the peculiarities of an in-shaping idea of Christianity, still linked to the Jewish roots of Jesus’ message. These texts have as well a specific disposition towards paganism, which openly recalls the question of the dispute between Peter and Paul and offers new elements for evaluating proto-Christian mentality. The apocryphal Acts of the Apostles highlight specific characters of the first hagiographical narratives, halfway between the production that will later become the commonly understood “hagiographic discourse” and the tradition of the late antique novel, but at the same time distinct from both these literary genres.